The Influence of Outdoor STEM Activities on Students’ STEM Literacy: A Study of Elective Subject, Extracurricular Activities, and Student Club - Pitiporntapin, Sasithep; Butkatanyoo, Oraphan; Piyapimonsit, Chatsiri; Thanarachataphoom, Thananun; Chotitham, Sareeya; Lalitpasan, Usanee (Universitas Negeri Semarang, 2024)
STEM literacy, the goal of STEM education, has shown potential for enhancement through outdoor activities in informal learning environments. However, the use of these activities in formal school settings to promote students’ STEM literacy remains unexplored. This research examined the STEM literacy of students participating in formal school settings through outdoor STEM activities across various contexts: elective subjects, extracurricular activities, and student clubs. The participants in this pre-experimental study included 29 students in elective subjects, 37 students in extracurricular activities, and 48 students in student clubs. The research instrument was a STEM literacy test comprising six open-ended questions to assess six components of STEM literacy: STEM concepts, STEM integration, STEM practice, STEM participation, STEM evaluation, and STEM awareness. Data were collected from students in each group before and after engaging in outdoor STEM activities using the STEM literacy test. Means (M) and standard deviations (SD) were used for data analysis. The findings revealed that students participating in student clubs had a higher mean STEM literacy score after learning (M=15.37, SD=3.71) compared to students in elective courses (M=14.62, SD=3.34) and extracurricular activities (M=10.30, SD=3.46). These results suggest that student clubs are the most effective method for promoting students’ STEM literacy. The researchers also provide recommendations for enhancing students’ STEM literacy through student clubs.